Investigating the performance of DSSC by incorporating modified Nanosilica surface in Polymer Gel Electrolyte - Coswald Stephen Sipaut @ Mohd Nasri; Rachel Fran Mansa; Jedol Dayou (Universiti Malaysia Sabah, 2014)
In this study, nanosilica or surface modified nanosilica were blended with polyethylene glycol (PEG), 4,4'-diphenylmethane diisocyanate (MDI) and propylene carbonate (PC) in order to form 3-dimensional polymer thin film which were capable to absorb and retain liquid electrolyte. Nanosilica was synthesized through modified stober method while the surface of synthesized nanosilica was modified with APTES through post modification method. The DSSCs were fabricated by using fluorine doped tin oxide coated glass slide (FTO) as substrate, titanium dioxide as semiconductor oxide thin film, N719 as sensitizer, and platinum coated FTO as counter electrode. Samples were characterized by using ATR-FTIR, nano zetasizer, and profilometer. Besides, the "liquid electrolyte absorbency and conductivity of the polymer thin films were measured. The photovoltaic performances of the DSSC based on SA-MDI-PEG polymer thin film showed the highest efficiency among the other polymer thin film, which was 2.79%.